Aspergilloma: Clinical Manifestation After Tuberculosis Infection - Winarni, Tika Wahyu; Erawati, Dini Rachma (International Journal of Radiology and Imaging, 2022)
Aspergilloma is a mass-like fungus ball consisting of Aspergillus fumigatus. Aspergilloma occurs in patients with pulmonary structural abnormalities in which the presence of a previous cavity is the predisposing factor that most often results in Aspergillus colonization, especially in tuberculosis endemic countries. 28 y.o andÂ  33 y.o female , complained of hemoptysis, chest pain, weight loss, and a history of TB treatment. The chest X-ray and CT scan revealed a solid lesion with an â€œAir-crescent signâ€ indicating Aspergilloma lesion. Patients were given symptomatic, anti-fungal drugs, and supportedÂ  by embolization procedure to reduce hemoptysis. The patient's condition began to improve after treatment. Imaging findings in x-rays and CT scans that point to Aspergilloma will help doctors in further management to provide a better prognosis for the patient.